2003
DOI: 10.1103/physrevb.67.235103
|View full text |Cite
|
Sign up to set email alerts
|

Band structure for a one-dimensional photonic crystal containing left-handed materials

Abstract: The explicit dispersion equation for a one-dimensional periodic structure with alternative layers of left-handed material (LHM) and right-handed material (RHM) is given and analyzed. Some abnormal phenomena such as spurious modes with complex frequencies, discrete modes and photon tunnelling modes are observed in the band structure. The existence of spurious modes with complex frequencies is a common problem in the calculation of the band structure for such a photonic crystal.Physical explanation and significa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(42 citation statements)
references
References 21 publications
2
39
0
1
Order By: Relevance
“…More importantly, a onedimensional stack of layers with alternating RH and LH material with vanishing average refractive index <n> displays a novel bandgap [8,9,10] that differs from a conventional Bragg reflection gap.…”
mentioning
confidence: 99%
“…More importantly, a onedimensional stack of layers with alternating RH and LH material with vanishing average refractive index <n> displays a novel bandgap [8,9,10] that differs from a conventional Bragg reflection gap.…”
mentioning
confidence: 99%
“…For layered structures containing LHMs and ordinary right-handed materials (RHMs), several results have been reported [7][8][9][10][11][12][13][14]. For example, unusual photon tunneling between two semi-infinite media separated by a RHM-LHM bilayer was found in the microwave regime [10].…”
Section: Introductionmentioning
confidence: 93%
“…Reference [14] explicitly demonstrates the existence of four types of bulk electromagnetic modes in periodic LHM/RHM arrays: the spurious modes, without physical meaning because they exhibit complex frequency, the discrete modes, real modes that appear at the center or the border of the Brillouin zone, the tunneling modes, characterized by evanescent (decreasing or increasing) fields in subsequent layers, and, the ordinary propagating modes. The same electromagnetic modes are expected even when absorption is not ignored [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…The dispersion relations, reflection characteristics, group velocities and n eff of the periodic structure contain negative index materials is calculated numerically using transfer matrix method [16,19,26]. The geometry of the structure under study is shown in Fig.…”
Section: Theorymentioning
confidence: 99%
“…They have shown that photon is tunneled through a much greater distance when a NIM has same magnitude of refraction index and thickness as those of the positive index material. Wu et al [16] have shown the dispersion relation of onedimensional periodic structure with alternate positive index material (PIM) and negative index material (NIM). The periodic structure has described unusual phenomena such as spurious modes with complex frequencies, discrete modes and photon tunneling modes.…”
Section: Introductionmentioning
confidence: 99%